Comparing error frequencies in first year ESL students / Noor Azli Affendy Lee - Affendy Lee, Noor Azli (Akademi Pengajian Bahasa, 2019)
There has been a considerable amount of research on the role of errors in ESL students' writing development. Recent studies generally investigated students' improvement in writing after a relatively short duration of exposure to an English course. The purpose of the current study is to analyse the error frequencies in written discourse made by one group of diploma level students at a Malaysian university throughout their first year of studies. Two writing samples were obtained from each student based on the writing assessments during their first two semesters of English core courses. The samples were keyed in into a corpus database and an analysis of error frequencies was conducted on each sample. By comparing errors made by the same students throughout their first year of study, this error frequency provides one important way to determine if there are any changes occurred in their written discourse during the chosen period of time. Results reported in this study revealed no significant changes in errors made by the same students in their subsequent written discourse. Findings are discussed in relation to the students' L2 proficiency development and the nature of their English learning experience.